Diversity and complexity of mouse allergens in urine, house dust, and allergen extracts assessed with an immuno‐allergomic approach. Issue 12 (28th November 2021) - Mindaye, Samuel T.; Sun, Carl; Esfahani, Sayyed Amin Zarkesh; Matsui, Elizabeth C.; Sheehan, Michael J.; Rabin, Ronald L.; Slater, Jay E.
Abstract: Background: Mouse allergy is an important cause of indoor asthma and allergic rhinoconjunctivitis. The major mouse allergen, Mus m 1, is a complex of homologous pheromone‐binding lipocalins called major urinary proteins (MUPs). Methods: We analyzed the proteome of MUPs in mouse urine, commercial mouse epithelial extracts, and environmental samples using several approaches. These include as follows: two‐dimensional electrophoresis and immunoblotting; liquid chromatography‐high‐resolution mass spectrometry (LC/HRMS); multiple reaction monitoring (MRM) mass spectrometry; and LC/HRMS analysis of glycans at the N‐66 residue of MUP3. Results: Albumin is predominant in the extracts, while MUPs are predominant in urine. LC/HRMS of 4 mouse allergen extracts revealed surprising heterogeneity. Of 22 known mouse MUPs, only 6 (MUP3, MUP4, MUP5, MUP13, MUP20, and MUP21) could be identified with MRM using unique peptides. Assessment of MUP content in urine, extracts, and dust samples showed good correlation between MRM and other methods working with different detection principles. All 6 identifiable MUPs were found in electrophoretically separated urine bands, but only MUP3 and MUP20 were above LOQ in unseparated mouse urine, and only MUP3, MUP4, and MUP20 were found in mouse epithelial extracts. Glycan heterogeneity was noted among 4 individual inbred mice: of 13 glycan structures detected, 8 were unique to one mouse, and only 2 glycan modifications were present in all 4 mice. Conclusions: Using mass spectrometry and MRM, mouse allergen extracts and urine samples are shown to be complex and heterogeneous. The efficacy and safety of commercial mouse allergen extracts will be improved with better controls of allergen content. Abstract : Commercial mouse epithelial extracts are heterogeneous, and their allergen profiles differ from mouse urine. The former contain predominantly albumin, the latter MUPs. MUPs are present in environmental dust. MUPs are expressed differentially in individual mice, in males and females, and in wild mice vs. inbred mice. Glycosylation of MUPs adds a further level of individualized complexity. Abbreviations: HRMS, high resolution mass spectrometry; LC, liquid chromatography; MRM, multiple reactions monitoring; MUP, major urinary proteins.